1965
DOI: 10.1084/jem.122.6.1161
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Demonstration of Cellular Sensitivity in Allergic Encephalomyelitis

Abstract: Peritoneal cells obtained from animals exhibiting delayed hypersensitivity are inhibited from migrating in vitro by specific sensitizing antigen. This test for the detection of delayed hypersensitivity was applied to the problem of cellular sensitivity in allergic encephalomyelitis (AE). The migration of peritoneal cells obtained from guinea pigs with AE was inhibited specifically by nervous tissue antigens. The specificity of this reaction was further studied. Neonatal rat nervous tissue, which was shown to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The studies in the animals immunized with the EP confirm and extend previous studies which have shown that animals immunized with brain antigens show delayed sensitivity in vivo and in vitro to the brain antigens (36)(37)(38). The lack of response of these animals to the encephalitogenic peptides in vivo and in vitro is in accord with expected results based on the principles of cellular immunity, since these peptides have amino acid sequences different from these in the immunizing protein.…”
Section: Discussionsupporting
confidence: 88%
“…The studies in the animals immunized with the EP confirm and extend previous studies which have shown that animals immunized with brain antigens show delayed sensitivity in vivo and in vitro to the brain antigens (36)(37)(38). The lack of response of these animals to the encephalitogenic peptides in vivo and in vitro is in accord with expected results based on the principles of cellular immunity, since these peptides have amino acid sequences different from these in the immunizing protein.…”
Section: Discussionsupporting
confidence: 88%
“…A purified cncephalitogen of human origin has also recently been shown to elicit positive skin tests in sensitized guinea pigs [2], D avid and Paterson [7] have shown cellular immunity in the guinea pig to a crude encephalitogcnic prep aration of guinea pig origin using the capillary migration inhibition assay. In order to work out an assay system in which it would be possible to study cellular immune responses to encephalitogens in human inflammatory, demyelinating disease, we have studied the transformation response in rodent lymphoid cells with a purified cncephalitogen of human origin.…”
mentioning
confidence: 99%
“…The technique therefore lends itself to the detection of delayed hypersensitivity in EAE and EAN, two experimental diseases considered to be mediated by this mechanism. Previous experiments using this method have shown positive inhibition of macrophage migration by lympho-cytes from guinea-pig and rats with EAE, using either crude brain or encephalitogenic protein as test antigen (David and Paterson, 1965;Brockman, Stiffey, and Tessar, 1968;Hughes and Field, 1968;Behan, Sheremata, Lamarche, Lisak, and Kies, 1970).…”
Section: Discussionmentioning
confidence: 99%